Development of a low background pulsed generator of intermediate energy range neutrons for remote detection of fissile materials - Chornyi, V.; Frolov, A.; Tsepilov, G.; Dubina, V.; Chornyi, A.; Solovyov, V. (Вопросы атомной науки и техники, 2004)
A structure of radiation shielding for a low background pulsed generator of intermediate energy range neutrons was developed on the basis of calculations and the data obtained in the model experiments, and limit parameters for remote detection of fissile materials using this generator were determined and are presented in this paper. The magnetically insulated diode structure and the radiation shielding geometry were optimized in accordance with the performed calculations.